B2B (Business to Business) Sale or Exclusive Licensing of a Software-Based Internet Platform: Target driven, legally certain and compliant development of a tailored agreement - Ulrich J. Grimm (European Institute for Knowledge & Value Management (EIKV), 2024)
The value of intangible properties for companies continues to increase. Intangible assets comprise, inter alia, patents, brand value, data, and software. Often, innova-tion activities resulted in in-house developed software-based internet platforms aimed at disrupting existing business models. A software-based internet platform consists of intellectual property in software (source code and object code, standard and individu-al, front-end and back-end), know-how, data and the trademark. Transferring usage rights on a software-based internet platform between businesses requires a license agreement once a decision on divestment of the in-house developed software-based internet platform has been made to allow for growth. By the means of a license, the intangible property rights can be exploited economically. A license agreement pro-vides plenty of flexibility. However, for a license many legal areas like the law of obli-gations, IP-rights, antitrust and competition laws, data protection laws, and other legal areas must be considered to legally authorize the usage of intangible assets, especial-ly in a B2B environment embedded in an international cross-border context. The challenge arises for maximizing the return on investment through efficient and com-pliant sale or exclusive licensing of the intellectual property while also targeting a prosperous future of the proficiently tailored software-based internet platform. A li-cense agreement has been developed based on a publicly available end-user license template. The license agreement defines in which form and to what extent (scope: exclusive, assignable, etc.) a licensor grants the licensee usage rights. Levers (com-mercial: license fee, success contribution, and investment) and options have been identified for the contract negotiation depending on the targets of the parties. The re-sult is a tailored license agreement for the transfer of a software-based internet plat-form in a cross-border B2B context that can be used as a template for companies facing a similar challenge. Following the described process, using tools in the form of an evaluation matrix, the executive summary or checklist, and most importantly the developed template license agreement the expectations of the parties will be met, the return on investment will be maximized, and excellent prospects for the in-house developed software-based internet platform will be provided.
Keywords: 330; License Agreement; Transfer Agreement; Software License; Intellectual Property; Intangible Assets; Internet Platform; B2B Contract Template; Scope of License; Targets and Process of Divestment; Levers for Negotiation; Evaluation Matrix; Executive Summary/Checklist